Anxiolytic-Like and Antinociceptive Effects of 2(S)-Neoponcirin in Mice - Julia Moreno; Norberto Manjarrez; Julia Cassani; Anna G. Escalona Araujo; Mariano Martínez-Vázquez; Rosa Estrada-Reyes (Molecules, 2013)
Study aims: 2(S)-neopincirin (NEO) is a constituent from of Clinopodium mexicanum, which is used in traditional Mexican herbal medicine for its tranquilizing and analgesic properties. This study investigated the anxiolytic-like, sedative and antinociceptive effects of NEO in several mice models. Material and methods: The anxiolytic-like effect was evaluated in the hole-board (HBT) and Open Field Tests (OFT); sedative effect was evaluated in sleeping time induced by sodium pentobarbital, and its antinociceptive actions were measured in the hot plate test. To evaluate if the GABA receptor could be involved in the anxiolytic-like effect produced by NEO, in independent experiments, the effects produced by co-administration of NEO plus muscimol (MUS) and NEO plus Pitrotoxin (PTX) were evaluated in the HBT. Results: NEO was isolated from Clinopodium mexicanum leaves. The NMR, MS and optic rotation data helped establish its identity as (2S)-5-hydroxy-4′-methoxyflavanone-7-O-{β-glucopyranosyl-(1→6)-β-rhamnoside}. NEO showed an anxiolytic-like effect and was able to counter the nociception induced by a thermal stimulus in a dose-dependent manner. PTX blocked the anxiolytic-like effect of NEO, while MUS was able to enhance it. Conclusions: The findings of present work demonstrated that NEO possesses anxiolytic-like and antinociceptive effects in mice. Such effects are not associated with changes in the locomotor activity. These results supported the notion that anxiolytic-like effect of NEO involves the participation of GABAergic system.